Estimation of the soil hazardous concentration of methylparaben using a species sensitivity approach. (November 2018) - Kim, Dokyung; Cui, Rongxue; Moon, Jongmin; Kwak, Jin Il; Kim, Shin Woong; Kim, Dasom; An, Youn-Joo
Abstract: Methylparaben, which is known to be an endocrine-disrupting chemical, is added to various personal care products, including cosmetics, and is also used as a food preservative and in pharmaceuticals. However, information on the toxicity of methylparaben in soil ecosystems is limited. Furthermore, unlike other substances such as metals and pesticides, there is no regulation of levels or safe concentrations of methylparaben in soil ecosystems. Therefore, the aims of this study were to evaluate the toxicity of methylparaben on soil species and to derive hazardous concentration (HC) values with respect soil ecosystem protection. We conducted acute bioassays on eight species within six taxonomic groups and chronic bioassays on five species within four taxonomic groups. On the basis of the results obtained, we derived an acute HC5 value of 44 mg/kg soil and a corresponding chronic value of 27 mg/kg soil for methylparaben using species sensitivity distribution methodology following Australian and New Zealand guidelines. Given that there has been no proposed standard value for methylparaben in soil in any country, it was not possible to compare the HC values calculated in this study with regulation standard levels. Nevertheless, to our knowledge, this study is first to assess the toxicity of methylparaben against soil-inhabiting species and to estimate acute and chronic HCs for soil fauna and flora. The results of this study will provide valuable fundamental data for the establishment of acceptable levels of methylparaben in soil. Graphical abstract: Image Highlights: Ecotoxicology assessment of methylparaben were performed using soil species. We derived soil methylparaben hazardous concentrations based on species sensitivity. Our results can be used to establish safe baseline concentrations for methylparaben. Abstract : This study estimates soil hazardous concentrations of methylparaben for protecting soil ecosystems based on species sensitivity methods.